Implementasi Model Delone and Mclean untuk Analisa Kepuasan Pengguna Aplikasi myIndihome - Dwi Atmoko (Jurnal Accounting Information System (AIMS), 2020)
The industrial revolution 4.0 has entered many lines of human life ranging from the internet and the creative and digital economy industries. The number of internet users is increasing from years to make Internet Service Providers (ISPs) competing against each other with various services and price choices that may vary. Indihome is one of the internet services provided by Telkom Indonesia. By the end of 2018, Indihome had up to 5 million customers making it the largest internet service provider with the largest number of customers in Indonesia. myIndiHome as an IndiHome internet service customer care application is the application with the highest number of downloads in Indonesia, with more than 1 million downloads. So that this study will test the level of user satisfaction myIndiHome application. This study uses the DeLone and McLean Model as a tool to analyze user satisfaction for the myIndiHome application. The DeLone model in this study uses the variables of information quality, service quality and system quality and user satisfaction. Results of this study note that the quality of myIndiHome application has a significant positive effect on user satisfaction and the quality of myIndiHome application system has a significant positive effect on user satisfaction. However, the quality of myIndiHome application services does not have a significant positive effect on user satisfaction.